Education Financing Management in Private Madrasah Ibtidaiyah - Rizki Akmalia Amal; Rini Dewi Andriani; Ahmad Zaki; Suparliadi Suparliadi; Candra Wijaya (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to determine the management of education financing applied at a private Madrasah Ibtidaiyah in  Pematangsiantar. This research uses qualitative research methods, with descriptive types of research. The subjects of this study are five people, namely the head of madrasah, treasurer, committee, Madrasah Foundation, and teacher. The study used primary data and secondary data as data sources. At the same time, collecting data through interviews, observations and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion withdrawal. Based on the findings, it was obtained that the management of education financing in madrasah always involves the head of the madrasah, madrasah treasurer, madrasah committee, foundation, and teachers. Sometimes, the proposed funds are not in accordance with its realization in its activities. Related to this, madrasah is assisted by a Monitoring and Evaluation Team, in this case, the Ministry of Religious Affairs of Pematang Siantar City, to oversee the form of reports to the foundation given quarterly.